Политика Уполномоченного По Правам Человека На Государственной Службе В Республике Татарстан, Россия (Policies of The Commissioner For Human Rights In Public Service In The Republic of Tatarstan, Russia) - Mladenov, Stanislav Vladimirov; Pertiwi, Gine Putri; Setiawan, Refly; Nur Faizah, Siti Indarini; Abdurrahman, Abdurrahman (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
AbstractThe Commissioner for Human Rights is a government institution that provides protection for the rights of the people in the Republic of Tatarstan, Russia. The establishment of the Human Rights Commissioner in the Russian Federation as a state body is one of the most important achievements of the transformation of democracy in Russia. In the Republic of Tatarstan, the Institute of Commissioners for Human Rights was established in 2000 in accordance with the Constitution of the Republic of Tatarstan to strengthen guarantees of state protection of human and civil rights and freedoms, to promote their observance and respect. by state agencies, local governments and officials. This study aims to explain how the Policies of the Commissioner for Human Rights in the Republic of Tatarstan are related to public services and to find out how the Commissioner for Human Rights of the Republic of Tatarstan provides the best service for the entire community. The method used in this research is a qualitative research method with a descriptive analysis approach. The results show that the Commissioner for Human Rights in the Republic of Tatarstan has made a policy that is appropriate for the welfare of the community and carries out its duties properly based on the main duties and functions of the Commissioner for Human Rights in the Republic of Tatarstan.Keywords: Policy, Commissioner for Human Rights, Public Services, Society of the Republic of Tatarstan, Russia AbstrakKomisaris Hak Asasi Manusia merupakan sebuah lembaga pemerintahan yang memberikan perlindungan terhadap hak masyarakat di Republik Tatarstan, Rusia. Pembentukan lembaga Komisaris Hak Asasi Manusia di Federasi Rusia sebagai badan negara merupakan salah satu capaian terpenting dari transformasi demokrasi di Rusia. Di Republik Tatarstan, Lembaga Komisaris Hak Asasi Manusia didirikan pada tahun 2000 sesuai dengan Konstitusi Republik Tatarstan untuk memperkuat jaminan perlindungan negara atas hak asasi dan kebebasan manusia dan sipil, untuk mempromosikan ketaatan dan penghormatan mereka. oleh badan-badan negara bagian, pemerintah daerah dan pejabat. Penelitian ini bertujuan untuk menjelaskan bagaimana Kebijakan Komisaris Hak Asasi Manusia di Republik Tatarstan terkait dengan pelayanan public dan untuk mengetahui bagaimana Komisaris Hak Asasi Manusia Republik Tatarstan dalam memberikan pelayanan yang terbaik bagi seluruh masyarakat. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan pendekatan deskriptif analisis. Hasil penelitian menunjukkan bahwa Komisaris Hak Asasi Manusia di Republik Tatarstan telah membuat suatu kebijakan yang tepat bagi kesejahteraan masyarakat dan menjalankan tugasnya dengan baik berdasarkan tugas pokok dan fungsi Komisaris Hak Asasi Manusia di Republik Tatarstan.Kata Kunci: Kebijakan, Komisaris Hak Asasi Manusia, Pelayanan Publik, Masyarakat Republik Tatarstan, Rusia АннотацияУполномоченный по правам человека - это государственное учреждение, обеспечивающее защиту прав людей в Республике Татарстан, Россия. Создание Уполномоченного по правам человека в Российской Федерации как государственного органа - одно из важнейших достижений трансформации демократии в России. В Республике Татарстан Институт уполномоченных по правам человека был создан в 2000 году в соответствии с Конституцией Республики Татарстан с целью усиления гарантий государственной защиты прав и свобод человека и гражданина, содействия их соблюдению и уважению. государственными органами, органами местного самоуправления и должностными лицами. Это исследование направлено на объяснение того, как политика Уполномоченного по правам человека в Республике Татарстан связана с государственными услугами, и на то, чтобы выяснить, как Уполномоченный по правам человека Республики Татарстан предоставляет наилучшие услуги для всего сообщества. Метод, использованный в этом исследовании, представляет собой качественный метод исследования с подходом описательного анализа. Результаты показывают, что Уполномоченный по правам человека в Республике Татарстан разработал политику, которая соответствует благосостоянию общества и выполняет свои обязанности должным образом, исходя из основных обязанностей и функций Уполномоченного по правам человека в Республике Татарстан. Татарстан.Ключевые слова: Политика, Уполномоченный по правам человека, Государственные службы, Общество Республики Татарстан, Россия